Surface plasmon resonance assisted optical characterization of nickel ion solution and nanocrystalline cellulose-graphene oxide thin film for sensitivity enhancement analysis - Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Fen, Yap Wing; Bashar Kamal Eddin, Faten; Abdullah, Jaafar; Mahdi, Mohd Adzir (Elsevier, 2022)
In this research, optical characterization of nickel ion solution and nanocrystalline cellulose-graphene oxide (NCC-GO) thin film has been carried out using surface plasmon resonance (SPR). The SPR experiments were carried out using bare gold thin film, in contact with deionized water and nickel ion at different concentrations, followed by the gold/NCC-GO system. Excellent agreement between the theoretical and experimental curves was observed where the real part (n) and the imaginary part (k) of the refractive index (ń) for gold thin film was . For nickel ion solution, the n value was similar with deionized water, i.e. 1.3333. Fitting the reflectance curves of gold/NCC-GO system revealed that ń for the NCC-GO thin film was . The analysis also showed the NCC-GO contributes to the sensitivity enhancement of SPR towards nickel ion sensing with a sensitivity of 10.8227°/RIU.